Characterisation of mycobacterial amidases and their role in bacterial growth and physiology - Senzani, Sibusiso (My University, 2018)
The genus Mycobacterium represents a complex family containing a number of clinically significant pathogens such as Mycobacterium ulcerans, Mycobacterium leprae and Mycobacterium tuberculosis (Mtb), the latter known to be the etiological agent of tuberculosis (TB). TB remains a global health issue, claiming approximately two million lives annually, with much of this burden being carried in the developing world in countries such as India and South Africa. The emergence of drug-resistant strains of Mtb and the synergistic relationship between TB and HIV/AIDS has crippled efforts to eradicate this disease by rendering many of the current therapeutics ineffective. This has created an urgent need for new drugs with novel modes of action and in this regard, peptidoglycan (PG)-associated enzymes constitute attractive targets for drug development. This study focused on a group of PG hydrolysing enzymes, the N-acetylmuramyl-L-alanine amidases (amidases), which have been linked to a number of essential cellular processes including cell division, antibiotic tolerance and pathogenicity in other organisms. Using the gene sequences of previously characterised cell wall amidases as queries, our bioinformatics analysis revealed that Mtb and Mycobacterium smegmatis contained 4 amidases, designated ami1-ami4. Analysis of an ami1 deficient M. smegmatis strain highlighted a role for this enzyme in cell division, cell elongation, cell shape maintenance and antibiotic tolerance. Deletion of ami1 resulted in the formation of chains consisting of 3 to 8 cells in approximately 20 % of the bacterial population assessed. Growth in these chains was characterised by ectopic mis-localisation of DivIVA, which resulted in the formation of lateral branches and Y-formed cell division. Single-cell localisation of the -sliding clamp (DnaN) and ParB, required for chromosome segregation, revealed that these ectopic branches were able to coordinate chromosome replication and partitioning. Additionally, increased cell permeability was noted in the Δami1 strain, which was associated with increased antibiotic susceptibility. These cell division defects were not observed in the Mtb Δami1 mutant. However, in this case, lateral growth appendages were observed under nutrient limited conditions. Deletion of ami1 in Mtb also resulted in a reduction in bacterial persistence upon challenge with isoniazid. In contrast, loss of ami4 in Mtb did not appear to have an impact on bacterial growth or survival rather, the mutant displayed increased survival under oxidative stress. The ami2 gene has been predicted to be essential, a hypothesis that was confirmed herein through the generation of a merodiploid strain wherein ami2 could be deleted. As such, characterisation of the role of Ami2 was conducted using a previously generated gene depletion strain. Depletion of Ami2 resulted in retarded growth, altered colony morphology, defective sliding motility, the formation of short cells and cells which contain bulges at the pole. Single-cell time lapse microscopy revealed that depletion of ami2 resulted in cessation of growth. Analysis of the localisation pattern of Ami2 revealed a polar localisation pattern, confirming a role for this enzyme in bacterial elongation. Collectively, these data highlight novel, specialist functions for mycobacterial amidases in cell elongation and division. The essentiality of Ami2 for mycobacterial growth also validates this enzyme as a possible drug target for TB.
A thesis submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy on medicine. Johannesburg, 2018.